NIVEL DE SATISFACCIÓN DEL USUARIO EXTERNO DE LOS SERVICIOS DE EMERGENCIA SANITARIOS DURANTE LA PANDEMIA DE LA COVID-19 (Enfermería Investiga, 2023)
RESUMEN  Palabras clave: personal de salud, pandemia, gestión de la calidad, sistemas de salud, atención médica ABSTRACT Introduction: The COVID-19 pandemic caused important challenges in medical care worldwide, affecting the perception of the quality of service. Objective: To assess the level of satisfaction of external users in relation to the perceived quality in the emergency service of the Quevedo General Hospital. Method: Quantitative approach research, non-experimental, descriptive cross-sectional design, non-probabilistic convenience sampling whose size was 73 users. The survey technique was used through the application of the questionnaire based on the SERVQUAL model (survey to measure service quality) modified and adapted with validation and reliability.Results: The largest number of users treated in the emergency service was male, the predominant age range was from 18 to 35 years, the predominant level of education was basic education, 41.1% have an occupation level of employee and 67.12% attend the public sector to attend to their state of health. The level of global dissatisfaction was 58.9%. The dimensions with the highest level of dissatisfaction corresponded to responsiveness and reliability. While the dimensions with the highest level of satisfaction concern tangibility and empathy.Conclusion: The pandemic behaved as a unique and disruptive unprecedented event in which no health system worldwide was prepared, nor was the Ecuadorian health system. This influenced the care of health professionals and the treatment of the user, being one of the reasons that contributed to the level of satisfaction. It is necessary for the hospital authorities to plan and coordinate their resources and capacities that contribute to improving medical care in times of health shock, such as those experienced during the pandemic.Keywords: Satisfaction, perceived quality, COVID-19, medical care, emergency service